2023
DOI: 10.3390/ma16072608
|View full text |Cite
|
Sign up to set email alerts
|

Ultimate Shear Force of an Any Anchor Group Post-Installed into Concrete

Abstract: This paper is devoted to the fastening system that consists of a number of anchors of approximately equal effective embedment depth, called “anchor group”, embedded into hardened concrete, used to transmit forces transverse to the anchors from an attachment to the concrete. The anchor group is far from the edges and is subjected to no more than marginal axial forces. Being post-installed, rather than cast-in, the embedded end of each anchor is not hooked, and no nuts, washers, or plates are attached to the emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Marinkovic et al [11] investigated the degree of damage in buildings after earthquakes and found that masonry infill walls, which were used in some elevator shaft areas instead of reinforced concrete shear walls, led to the insufficient seismic performance of the structures. Some studies on post-installed concrete anchors [12] and the seismic analysis of existing reinforced buildings [13] provide a reference for the mechanical performance analysis of the post-installed elevator shafts of existing buildings. Zhou et al [14] studied the seismic performance of a light wood structure and found that the use of a masonry elevator shaft in a light wood structure can significantly reduce the displacement at the top of the structure and improve seismic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Marinkovic et al [11] investigated the degree of damage in buildings after earthquakes and found that masonry infill walls, which were used in some elevator shaft areas instead of reinforced concrete shear walls, led to the insufficient seismic performance of the structures. Some studies on post-installed concrete anchors [12] and the seismic analysis of existing reinforced buildings [13] provide a reference for the mechanical performance analysis of the post-installed elevator shafts of existing buildings. Zhou et al [14] studied the seismic performance of a light wood structure and found that the use of a masonry elevator shaft in a light wood structure can significantly reduce the displacement at the top of the structure and improve seismic performance.…”
Section: Introductionmentioning
confidence: 99%